Is the Burden Too Small? – Effective Tax Rates in Ghana - David Nguyen-Thanh; Christoph Strupat (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
This paper examines capital income taxation in Ghana. We calculate effective marginal tax rates (EMTR) and effective average tax rates (EATR) using an extended Devereux-Griffith methodology to accommodate for tax incentives - an exercise that has not been done so far for Ghana. We find that the wide range of tax incentives leads to a high variation of effective average tax rates in Ghana. Tax holidays and preferential income tax rates lower the effective tax burden to a significant extent and encourage individual tax avoidance strategies. Furthermore our results confirm previous findings that tax holidays, effectively reducing EATR, favor high-profit short-lived investment projects raising doubts about their rationale. – – Dieses Papier untersucht die effektive Unternehmenssteuerbelastung in Ghana. Dazu wurden marginale und durchschnittliche effektive Unternehmenssteuersätze nach der von Devereux und Griffith entwickelten Methodologie berechnet. Die Ergebnisse der Untersuchung zeigen, dass die hohe Anzahl von Steuererleichterungen zu großen Unterschieden in der effektiven Steuerbelastung zwischen den Unternehmen führen. Insbesondere die steuerliche Bevorzugung von multinationalen Unternehmen durch jährliche Steuerbefreiung oder stark reduzierte Steuersätze senkt deren effektive Steuerbelastung. Im Vergleich mit anderen afrikanischen Ländern liegt die effektive Unternehmenssteuerbelastung in Ghana deutlich unter dem Durchschnitt.
Keywords: H23; H25; H10; 330; effective tax rates; tax holidays; Ghana